Digital Financial Reporting di Bawaslu Provinsi Bali - Ni Luh Made Hendriyani (Universitas Pendidikan Nasional, 2018)
ABSTRACTThe purpose of this research is to know the role and implementation of information technology in the process of financial management and preparation of financial statements in Bawaslu Province Bali. The informant in this research is the treasurer and financial management staff in Bawaslu Bali Province and treasurer and management staff at Panwaslu Singaraja, Klungkung and Denpasar. Technic data collection used is interview and documentation. The results of this study indicate that the role and implementation of technology is very easy and effective in the process of management and preparation of financial statements in Bali Province Bawaslu but can not be denied that the HR also affects the running of the financial management process to accountable, transparent and accountable financial statements.